Behavior of Reinforced Concrete Deep Beams with Openings under Vertical Loads Using Strut and Tie Model - Rasha T. S. Mabrouk; Mahmoud A. S. Mahmoud; Magdy E. Kassem (Civil Engineering Journal, 2021)
This research aims to study the effects of the size and location of openings on deep beams. The analysis of deep beams with openings presents a rather complex problem for engineers, as there are currently no guidelines within the design codes for this problem. Using the strut and tie model is a feasible solution, but also gives some uncertainties due to the various models that can be used. This paper proposes using a strut and tie model for the deep beams with openings where reinforcement is laid out in the form of embedded struts and ties. The study is divided into an experimental and a numerical part. The experimental study was conducted on eight reinforced concrete deep beams under vertical loads. Seven of the beams had web openings of different sizes and locations, while the eighth specimen was a reference beam without any openings. The beams had the same concrete dimensions with the size of the openings in the web taken as 150 150 mm and 300 300 mm, and the location of the opening in the horizontal direction was varied between 0.11 to 0.4 the span. The experimental results were analyzed in terms of cracking pattern, mode of failure, and load-deflection behavior and then compared to numerical analysis conducted using a finite element program. A parametric study followed to investigate the influence of reinforcement arrangement and reinforcement around the openings on the behavior of deep beams. The results showed that large web openings that directly interrupted the compression strut had the most reduction in beam capacity and that the location of the opening did not significantly affect the strength of the beam in the case of small openings. Doi: 10.28991/CEJ-SP2021-07-011 Full Text: PDF